(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: The COVID-19 pandemic has likely affected the already high unmet need for family planning in low and middle-income countries. This qualitative approach was used to explore the possible ways in which the COVID-19 pandemic, including the impact of a 3-month government mandated lockdown, might affect family planning outcomes in Punjab, Pakistan. A secondary aim was to elicit recommendations to improve family planning service delivery in the context of COVID-19. Methods: Eight focus group discussions were conducted with men and women separately. The target Population were married women and men (N 64) who were using any short-term contraceptive methods (i.e., Injectable, Oral Pills and Condom) and 06 key-informant interviews were also conducted with the stakeholders of Department of Health and Population Welfare Department, Punjab. Data were analyzed using thematic analysis. Results: It was identified that a significant disruption to the delivery of family planning services due to COVID-19, with potential negative effects on contraceptive use and risk for unintended pregnancy. COVID-19 had a negative effect on individual enabling factors such as family income, affecting service access, and on community enabling factors, such as transportation barriers and the disruption of community-based family planning delivery through village health teams and mobile clinics. Participants felt COVID-19 lockdown restrictions exacerbated existing contextual predisposing factors related to poverty and gender inequity, such as intimate partner violence and power inequities that diminish women’s ability to refuse sex with their husband and their autonomy to use contraceptives. Recommendations to improve family planning service delivery in the context of COVID-19 centered on emergency preparedness, strengthening community health systems, and creating new ways to safely deliver contractive methods directly to communities during future COVID-19 lockdowns. Conclusions: This study highlights the consequences of COVID-19 lockdown on family planning distribution, as well as the exacerbation of gender inequities that limit women’s autonomy in pregnancy prevention measures. To improve family planning service uptake in the context of COVID-19, there is a need to strengthen emergency preparedness and response, utilize community structures for contraceptive delivery, and address the underlying gender inequities that affect care seeking and service utilization.